2014
DOI: 10.3109/13880209.2014.935865
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic biomonitoring of pirethroid insecticides in human lymphocyte cultures: Use of micronuclei as biomarkers and recovery byRosa caninaextracts of mutagenic effects

Abstract: Context: Insecticides are used to control pests. Cypermethrin and fenvalerate are widely used pirethroid insecticides in the world. Rosa canina L. (Rosaceae) is used as a traditional medicinal plant against viral infections and disorders of the kidneys and urinary tract due to its high vitamin C level. Objective: The genotoxic effects of cypermethrin and fenvalerate were examined with the micronucleus (MN) test. Then, we determined the ability of the water (RC wtr ) and ethanol (RC eta ) extracts of rosehip (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…In addition, it has been shown that profenofos, an organophosphate insecticide, increased the micronucleus frequency in human peripheral lymphocyte cells and decreased the nuclear division index (0.25, 0.5, 0.75 and 1.0 μg/mL) at different concentrations ( Kasımoğlu and Uysal, 2014 ). In another study of antioxidant enzyme levels with chlorpyrifos-ethyl from organophosphate insecticides, it has been found that the paraoxonase activity and total antioxidant levels decreased while the levels of oxidative stress index and total oxidant increased ( Deveci et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it has been shown that profenofos, an organophosphate insecticide, increased the micronucleus frequency in human peripheral lymphocyte cells and decreased the nuclear division index (0.25, 0.5, 0.75 and 1.0 μg/mL) at different concentrations ( Kasımoğlu and Uysal, 2014 ). In another study of antioxidant enzyme levels with chlorpyrifos-ethyl from organophosphate insecticides, it has been found that the paraoxonase activity and total antioxidant levels decreased while the levels of oxidative stress index and total oxidant increased ( Deveci et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the other compund, beta carotene in R. canina was shown to decrease the genotoxic effects of doxorubicin in this fruit fly ( Dias et al., 2009 ). It was found that the ethanol and water extracts of R. canina reduced the genetic damages in the human lymphocyte cells induced by cypermethrin and fenvalerate insecticides exposures and in the D. melanogaster induced by EMS exposure ( Kızılet et al., 2013 ; Kasımoğlu and Uysal, 2014 ). Ramos et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kızılet et al [31], kanat benek testini (SMART) kullanarak yaptıkları çalışmada, kuşburnu etanol ekstresinin etil metansülfonatın (EMS) mutajenik etkilerini azalttığını rapor etmişlerdir. Bir başka çalışmada ise sipermetrin ve fenvalerat insektisitlerinin genotoksik etkileri kuşburnu bitkisine ait ekstreler ile giderilmiştir [32]. Kılıçgün and Dehen [33] in vitro test sistemleri ile kuşburnunun DNA hasarı üzerine koruyucu etkilerini araştırmışlar ve % 3'lük uygulama ile protein oksidasyonu, lipit peroksidasyonu ve DNA hasarının belirgin şekilde inhibe olduğunu belirtmişlerdir.…”
Section: Discussionunclassified
“…Uysal [28] expressed that both water and ethanol extract of the rosehip removed mutagenic effects of cypermethrin and fenvalerate insecticides in the human peripheral lymphocytes.…”
Section: Discussionmentioning
confidence: 99%